Sosialisasi Pemakaian Dan Pemberian Obat Cacing Pada Balita Di Posyandu Bougenville IV Tiban Baru - Suci Fitriani Sammulia; Yunisa Friscia Yusri; Arie Vonikartika; Habibie Deswilyaz Ghiffari; Komang Natalia Fitriani; Lupina Lupina (Jurnal Pengabdian Ilmu Kesehatan, 2021)
Soil Transmissible Helminthiasis (STH) is still a public health problem in countries with tropical and sub-tropical climates, including Indonesia. The prevalence of worms in Indonesia currently ranges from 20-86 percent with an average of 30 percent. This frequently occurring disease really disrupts children's growth and development. Worm control efforts are directed at breaking the chain of transmission of worms, namely the toddler and school age groups, with 1 ) administer medicationmass prevention of worms in vulnerable groups to stop the spread of worm eggs from sufferers to the surrounding environment, 2) improving sanitation hygiene, and 3) cultivating clean and healthy living behavior through health promotion. Through this community service activity, socialization activities on the use and administration of worm medicine have been implemented. In Toddlers at Posyandu Bougenville IV, Tiban Baru. This activity is useful for children under five so that they always receive worm medicine and socialize and increase mothers' understanding about how important it is to give worm medicine to toddlers. Activities to socialize the use and administration of worm medicine to toddlers can increase public knowledge. There are still some people, especially mothers with toddlers, who rarely give them worm medicine.